Analisis Kebijakan dan Penegakan Hukum Pidana Transnasional Tindak Pidana Perdagangan Narkotika di Asia Tenggara - Fakhry Qolby Aminullah Fikri (Terekam Jejak Publisher, 2024)
Drug trafficking is one of the biggest challenges faced by ASEAN countries. This crime is very complicated because it often involves international networks. To deal with it, ASEAN countries need to work together and have comprehensive policies. This article aims to look at the policies and law enforcement used by ASEAN countries to tackle drug trafficking. The study uses a qualitative approach to explore different national policies and regional cooperation frameworks. Information was gathered from books, websites, and journal articles. The research shows that while countries have different ways of dealing with drugs, ASEAN cooperation plays a crucial role in strengthening law enforcement and reducing drug circulation. However, challenges like different legal systems, limited resources, and lack of coordination are still big problems. The article concludes that improving regional coordination, harmonizing policies, and boosting law enforcement capabilities are important steps to fight drug trafficking in ASEAN.